Diastereoselective Synthesis and Biological Evaluation of Spiro[chromane-2,4′-pyrimidin]-2′(3′H)-ones as Novel Antimicrobial and Antioxidant Agents - Alena S. Karandeeva; Natalia A. Bogdanova; Mariya V. Kabanova; Sergey I. Filimonov; Zhanna V. Chirkova; Anna A. Romanycheva; Valeria A. Panova; Anton A. Shetnev; Nurila A. Togyzbayeva; Saken A. Kanzhar; Nurbol O. Appazov; Kyrill Yu. Suponitsky (Molecules, 2025)
This study reports an improved diastereoselective synthesis of substituted spiro[chromane-2,4′-pyrimidin]-2′(3′H)-ones via the acid-catalyzed condensation of 6-styryl-4-aryldihydropyrimidin-2-ones with resorcinol, 2-methylresorcinol, and pyrogallol. The optimized method allows for the isolation of diastereomerically pure products, with stereoselectivity controlled by varying acid catalysts (e.g., methanesulfonic acid vs. toluenesulfonic acid) and solvent conditions. The synthesized compounds were evaluated for antimicrobial and antioxidant activities. Notably, the (2S*,4R*,6′R*)-diastereomers exhibited significant antibacterial activity against both Gram-positive and Gram-negative bacterial strains with minimal inhibition concentration down to 2 µg/mL, while derivatives containing vicinal bisphenol moieties demonstrated potent antioxidant activity, with IC50 values (12.5 µg/mL) comparable to ascorbic acid. Pharmacokinetic analysis of selected hit compounds revealed favorable drug-like properties, including high gastrointestinal absorption and blood-brain barrier permeability. These findings highlight the potential of spirochromane-pyrimidine hybrids as promising candidates for further development in the treatment of infectious diseases and oxidative stress-related pathologies.